2022
DOI: 10.1177/02557614221110952
|View full text |Cite
|
Sign up to set email alerts
|

Teaching songs from diverse cultures to pre-service teachers using a “Four Step Flipped” method

Abstract: As music educators around the globe continue to work in blended environments, it is important to explore how pedagogical approaches can be adapted and reimagined in ways that enhance teaching and learning in this changing educational landscape. In this study, the authors drew on elements of Collaborative Online International Learning (COIL) to teach three culturally diverse songs to pre-service teachers at a Spanish university. Acting as culture bearers and tertiary music educators, they selected and taught so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
1
0
3
Order By: Relevance
“…This method can be adopted for online teaching as well, especially when using an LMS to provide required content for learning beforehand. Flipping materials help students to explore and study the content before coming to the online class (Nethsinghe et al, 2022). Recent research on the flipped classroom and medical education has suggested that knowledge, skills, and behavior change with the flipped classroom curriculum (Goldberg, 2014;Persky & McLaughlin, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This method can be adopted for online teaching as well, especially when using an LMS to provide required content for learning beforehand. Flipping materials help students to explore and study the content before coming to the online class (Nethsinghe et al, 2022). Recent research on the flipped classroom and medical education has suggested that knowledge, skills, and behavior change with the flipped classroom curriculum (Goldberg, 2014;Persky & McLaughlin, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…La educación musical es especialmente sensible a este aspecto (Shaw y Mayo, 2021). El Four Step Flipped Method (Nethsinghe et al, 2023) resultó ser un enfoque educativo útil para generar situaciones de aprendizaje que permitan al alumnado desarrollar conocimientos y habilidades relacionadas con el aprendizaje de la música y modelos educativos preocupados con la inclusión y que potencien el cultivo de una mentalidad global en el estudiantado (Mellizo y Cabedo-Mas, 2022).…”
Section: Discussionunclassified
“…El alumnado valoró el entorno en línea como una forma de abrir nuevas ventanas de oportunidades para interactuar con mediadores culturales en tiempo real (Nethsinghe et al, 2023). Si bien existen innumerables beneficios y desventajas de la enseñanza y el aprendizaje en línea, los autores señalan el Four Step Flipped Method como un posible modelo para vehicular la enseñanza colaborativa transnacional en entornos híbridos.…”
Section: Discussionunclassified
See 1 more Smart Citation